Degradable anti-inflammatory bone fracture plate and preparation method thereof

By combining the magnesium alloy matrix with polylactic acid anti-inflammatory coating, a degradable anti-inflammatory bone plate was prepared, which solved the problem of non-degradable and insufficient service life of the existing bone plate system materials, and achieved the degradability and resistance of the bone plate plate. and adapt to the needs of different patients.

CN119424772AInactive Publication Date: 2025-02-14OLYDE (GUANGZHOU) TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411298741.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing degradable osteotomy plate systems have problems such as non-degradable materials, difficulty in repairing and insufficient service life, and are especially not suitable for patients with osteoporosis.

Method used

The design of combining the magnesium alloy matrix with polylactic acid anti-inflammatory coating is adopted, and by adjusting the synthesis process of polylactic acid and the combination of coating, degradable anti-inflammatory bone plates with different degradation times are prepared.

Benefits of technology

The degradability and anti-inflammatory effect of the bone plate is achieved, the degradation time of the magnesium alloy matrix is ​​extended, the fracture toughness is improved, and the needs of different patients are adapted to the needs of different coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005046939760000101
    Figure BDA0005046939760000101
  • Figure BDA0005046939760000111
    Figure BDA0005046939760000111
Patent Text Reader

Abstract

The invention provides a degradable anti-inflammatory bone fracture plate and a preparation method thereof. The degradable anti-inflammatory bone fracture plate is obtained by spraying a polylactic acid anti-inflammatory coating on a magnesium alloy base material. By adjusting the synthesis process of polylactic acid, polylactic acid with different molecular weights and different molecular weight distribution widths is obtained, the spraying sequence and the number of layers are determined according to different degradation times of polylactic acid, and the degradable anti-inflammatory bone fracture plate with different degradation times is obtained so as to meet the requirements of different patients. And the polylactic acid coating with the high molecular weight is sprayed on the magnesium alloy base material, so that the fracture toughness of the magnesium alloy base material can be improved to a certain extent. As each coating contains the anti-inflammatory drug, the degradation time of the coating with high molecular weight and narrow molecular weight distribution width of the polylactic acid is obviously longer than that of the coating with low molecular weight and wide molecular weight distribution width of the polylactic acid, and the anti-inflammatory drug contained in the coating can be released as expected through the combination of different coatings; the bone fracture plate product is ensured to have a good anti-inflammatory effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bone plate instruments for fracture fixation, and in particular relates to a degradable anti-inflammatory bone plate and a preparation method thereof. Background Art

[0002] Due to their lifespan, traumatic implants generally need to be removed after bone healing. If they are not removed in time, the implant may exceed its service life and be damaged, causing harm to the body. Removal will create new wounds, causing secondary pain and another period of recovery and healing. Therefore, degradable bone plate systems have become an important development direction for the industry.

[0003] There are many types of degradable bone fixation materials, including minerals, polymer materials, and degradable metal materials such as magnesium alloys and iron alloys. Common medical degradable polymer materials include polylactic acid (PLA), polyglycolic acid (PGA), and its copolymers (PLGA), polycaprolactone and polydioxanone, among which polylactic acid (PLA), polyglycolic acid (PGA) and its copolymers (PLGA) are more widely used. Among them, polylactic acid includes PLLA and PDLA. High molecular weight polylactic acid degrades slowly and will remain in the body for a long time. In addition, the local acidic environment produced by the degradation of polylactic acid internal fixation parts in the body can easily cause aseptic inflammation of bone tissue and affect the formation of new bone. In addition, the mechanical strength of polylactic acid fixation parts is insufficient and lacks bone bonding ability. Therefore, the modification of polylactic acid to improve its related properties has become a research hotspot. The main purpose of the modification is to enhance the mechanical strength of the material, control its degradation rate, and neutralize the acidity of the degradation products to make it more biocompatible.

[0004] Chinese patent (CN202311635829.4, publication date: March 29, 2024) discloses a degradable bone plate system, a preparation method of the degradable bone plate system, and a control method of the degradable bone plate system, the system includes a degradable bone plate, a degradable bone screw, a flexible piezoelectric plugging head, a degradable stress sensor, and a micro power supply and a controller; the materials of the degradable bone plate and the degradable bone screw are polylactic acid / magnesium oxide nanoparticles / phosphate glass fiber composite materials, the degradable stress sensors are distributed on the side of the degradable bone plate, and the micro power supply and controller are placed in the patient's subcutaneous fat layer. The bone plate system uses non-degradable materials such as phosphate glass fiber, and adopts devices such as a micro power supply, a controller, and a flexible piezoelectric plugging head. Once a fault occurs, it is difficult to repair.

[0005] A Chinese patent (CN201810492330.5, authorization announcement date: April 26, 2022) discloses a magnesium alloy fixing screw that can be controlled to degrade in vivo, and its preparation method includes the following steps: (1) using magnesium alloy to process into a screw body; (2) forming an oxide film layer with a thickness of 50 to 200 μm on the magnesium alloy screw body by an alternating current oxidation process; (3) applying a degradable polymer coating with a thickness of 1 to 50 μm on the oxide film layer by dip coating or spraying. The strength retention period of the fixing screw is about 3 months, and the degradation cycle can be controlled to about 6 to 8 months. It can be seen that the use of the fixing screw is limited to a repair period of about three months, which is not suitable for patients with osteoporosis, and the application scenarios are limited. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the technical solution provided by the present invention is:

[0007] The degradable anti-inflammatory bone fracture plate provided by the present invention comprises a magnesium alloy substrate and a polylactic acid anti-inflammatory coating coated on the surface thereof, and the preparation method thereof comprises the following steps:

[0008] S1: Preparation of polylactic acid: Dehydrate the lactic acid raw material at 110-140° C. for 5-8 hours to obtain lactic acid oligomers, add a catalyst to the lactic acid oligomers at 100-120° C. under inert atmosphere protection and stir for 1-3 hours, continue to heat to 160-200° C., and polycondense under vacuum conditions for 10-20 hours to obtain polylactic acid, wherein the catalyst is any one of tin chloride, stannous chloride, and stannous lactate;

[0009] S2: Screening of polylactic acid: by adjusting the reaction temperature and time during polycondensation, polylactic acid with different molecular weights and molecular weight distribution widths is obtained, and polylactic acid with a molecular weight distribution index of 1.5-5.0, a weight average molecular weight of 50,000-300,000, and a high molecular weight tailing index greater than 2.5 in the molecular weight distribution width is screened for subsequent processes;

[0010] S3: Preparation of polylactic acid anti-inflammatory coating: The polylactic acid screened in S2 is mixed with an anti-inflammatory drug, wherein the anti-inflammatory drug is one or more of aspirin, naproxen, indomethacin, meloxicam, celecoxib, diclofenac sodium, nimesulide, and etoricoxib, and the mixture is sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, and the spraying thickness is 5-10 μm;

[0011] S4: Degradation performance test: artificial plasma was used to simulate the human body environment, and the magnesium alloy substrate sprayed with the degradable anti-inflammatory coating was placed in the artificial plasma to test the degradation time of each composition. The polylactic acid and anti-inflammatory drug blends were numbered as P1, P2...P10 according to the degradation time from short to long, and finally 10 groups of mixtures were screened;

[0012] S5: Take the prepared magnesium alloy substrate, and according to specific usage requirements, spray 1-30 layers of the composition of polylactic acid and anti-inflammatory drugs on the magnesium alloy substrate by ultrasonic spraying, and dry each sprayed layer before spraying the next layer. The thickness of the polylactic acid anti-inflammatory coating is 5-300μm. According to specific usage requirements, select a suitable combination from P1, P2...P10 and spray them in order to obtain a degradable anti-inflammatory bone plate.

[0013] Among them, the zinc content in the magnesium alloy matrix is ​​not higher than 0.20wt%, the lithium content is not higher than 0.20wt%, the manganese content is not higher than 0.15wt%, the copper content is not higher than 0.03wt%, the iron content is not higher than 0.01wt%, the silicon content is not higher than 0.01wt%, and the nickel content is not higher than 0.005wt%.

[0014] Compared with the prior art, the present invention has the following advantages: 1. The present invention obtains polylactic acid with different molecular weights and different molecular weight distribution widths by adjusting the synthesis process of polylactic acid, and determines the spraying order and number of layers according to its different degradation times to obtain degradable anti-inflammatory bone fracture plates with different degradation times to meet the needs of different patients; 2. The polymer tailing index in the molecular weight distribution width is greater than 2.5, indicating that the proportion of high molecular weight polymers in polylactic acid is relatively high, which can improve the fracture toughness of the magnesium alloy matrix to a certain extent; 3. Since each coating contains anti-inflammatory drugs, the degradation time of the coating with high molecular weight and narrow molecular weight distribution width of the polylactic acid used is significantly longer than that of the coating with low molecular weight and wide molecular weight distribution width of the polylactic acid used. Through the combination of different coatings, the coating with high molecular weight and narrow molecular weight distribution width of the polylactic acid can play a certain protective role on the coating covered by it, so that the anti-inflammatory drugs contained therein are released as expected, ensuring that the bone fracture plate product has a good anti-inflammatory effect. DETAILED DESCRIPTION

[0015] Next, embodiments of the present invention will be described.

[0016] Embodiment 1:

[0017] The lactic acid raw material was dehydrated and reacted at 110°C for 8 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 1 hour by adding tin chloride catalyst under argon protection at 120°C, and then the temperature was continued to rise to 200°C, and polycondensed under vacuum conditions for 10 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above polylactic acid and aspirin were blended in a ratio of 100:1 by weight, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 5μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0018] Embodiment 2:

[0019] The lactic acid raw material was dehydrated and reacted at 120°C for 7 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 2 hours at 110°C under argon protection by adding tin chloride catalyst, and then the temperature was continued to rise to 200°C, and polycondensed under vacuum conditions for 12 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The polylactic acid and naproxen were blended in a weight ratio of 100:1, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 5μm. The magnesium alloy substrate sprayed with the degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0020] Embodiment 3:

[0021] The lactic acid raw material was dehydrated and reacted at 130°C for 6 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 3 hours at 100°C under argon protection by adding tin chloride catalyst, and then the temperature was continued to rise to 200°C, and polycondensed under vacuum conditions for 14 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above polylactic acid and indomethacin were blended in a weight ratio of 100:1, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 5μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0022] Embodiment 4:

[0023] The lactic acid raw material was dehydrated and reacted at 140°C for 5 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 3 hours by adding tin chloride catalyst at 110°C under argon protection, and then the temperature was continued to rise to 200°C, and polycondensed under vacuum conditions for 20 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above-mentioned polylactic acid and meloxicam were blended in a weight ratio of 100:1, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 5μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0024] Embodiment 5:

[0025] The lactic acid raw material was dehydrated and reacted at 110°C for 8h to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 1h by adding stannous chloride catalyst under argon protection at 120°C, and then the temperature was continued to rise to 180°C, and polycondensed under vacuum for 10h to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above-mentioned polylactic acid and celecoxib were blended in a ratio of 100:1 by weight, and the blend was sprayed on the surface of the magnesium alloy substrate by ultrasonic spraying, and the spraying thickness was 8μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0026] Embodiment 6:

[0027] The lactic acid raw material was dehydrated and reacted at 130°C for 6 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 2 hours by adding stannous chloride catalyst at 110°C under argon protection, and then the temperature was continued to rise to 180°C, and polycondensed under vacuum conditions for 15 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above-mentioned polylactic acid and diclofenac sodium were blended in a ratio of 100:1 by weight, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 8μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0028] Embodiment 7:

[0029] The lactic acid raw material was dehydrated and reacted at 140°C for 7 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 2 hours by adding stannous chloride catalyst at 100°C under argon protection, and then the temperature was continued to rise to 180°C, and polycondensed under vacuum conditions for 18 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above polylactic acid and nimesulide were blended in a weight ratio of 100:1, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 8μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0030] Embodiment 8:

[0031] The lactic acid raw material was dehydrated and reacted at 130°C for 8 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 3 hours by adding stannous chloride catalyst under argon protection at 110°C, and then the temperature was continued to rise to 180°C, and polycondensed under vacuum conditions for 20 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above-mentioned polylactic acid and etoricoxib were blended in a ratio of 100:1 by weight, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 8μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0032] Embodiment 9:

[0033] The lactic acid raw material was dehydrated and reacted at 120°C for 8 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 2 hours at 110°C under argon protection by adding stannous lactate catalyst, and then the temperature was continued to rise to 160°C, and polycondensed under vacuum conditions for 10 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above polylactic acid and aspirin were blended in a ratio of 100:1 by weight, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 10μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0034] Embodiment 10:

[0035] The lactic acid raw material was dehydrated and reacted at 140°C for 6 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 1 hour by adding stannous lactate catalyst under argon protection at 120°C, and then the temperature was continued to rise to 160°C, and polycondensed under vacuum conditions for 12 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The polylactic acid and naproxen were blended in a weight ratio of 100:1, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 10 μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0036] Embodiment 11:

[0037] The lactic acid raw material was dehydrated and reacted at 120°C for 5 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 1 hour by adding stannous lactate catalyst under argon protection at 100°C, and then the temperature was continued to rise to 160°C, and polycondensed under vacuum conditions for 16 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above polylactic acid and indomethacin were blended in a weight ratio of 100:1, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 10μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of the composition.

[0038] Embodiment 12:

[0039] The lactic acid raw material was dehydrated and reacted at 130°C for 7 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 3 hours by adding tin chloride catalyst at 100°C under argon protection, and then the temperature was continued to rise to 160°C, and polycondensed under vacuum conditions for 20 hours to obtain polylactic acid; the molecular weight distribution index, weight average molecular weight, and polymer tailing index in the molecular weight distribution width of the polylactic acid were measured. The above-mentioned polylactic acid and meloxicam were blended in a weight ratio of 100:1, and the blend was sprayed onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 10μm. The magnesium alloy substrate sprayed with a degradable anti-inflammatory coating was placed in artificial plasma to test the degradation time of each composition.

[0040] The magnesium alloy substrates used in the above embodiments are all products from the same batch, wherein the impurity detection results are: zinc content 0.17wt%, lithium content 0.14wt%, manganese content 0.15wt%, copper content 0.02wt%, iron content 0.01wt%, silicon content 0.008wt%, and nickel content 0.003wt%. An uncoated magnesium alloy substrate is selected as a comparative example.

[0041] In each of the above embodiments and comparative examples, three identical samples were prepared in each group, and the samples were immersed in artificial plasma, which was replaced every 24 hours. The samples were weighed every day, and the time for the sample to degrade to 30% of the initial weight was recorded as the degradation time.

[0042] The specific test data are shown in the following table:

[0043] Table 1 Test data table

[0044] Weight average molecular weight Distribution Width Tailing Index Degradation time serial number Example 1 90000 1.28 2.6 151d P1 Example 2 85000 1.21 2.6 132d P2 Example 3 85000 1.17 2.4 130d / Example 4 70000 1.24 2.5 119d P3 Example 5 140000 1.09 2.9 179d P4 Example 6 170000 1.11 2.6 173d P5 Example 7 180000 1.14 2.5 170d P6 Example 8 205000 1.12 2.8 181d P7 Example 9 80000 1.18 2.7 143d P8 Example 10 65000 1.13 2.6 139d P9 Embodiment 11 55000 1.07 2.3 116d / Example 12 65000 1.11 2.5 128d P10 Comparative Example 1 / / / 109d /

[0045] From the above data, it can be seen that the larger the molecular weight and the narrower the molecular weight distribution, the slower the degradation rate of the sample; the smaller the molecular weight and the wider the molecular weight distribution width, the faster the degradation rate of the sample, but the degradation time of the coated samples is slower than that of the uncoated samples, indicating that the coating provided by the present invention has a significant effect on prolonging the degradation time of the magnesium alloy substrate.

[0046] The following examples illustrate the changes in the mechanical strength of the bone fracture plate provided by the present invention.

[0047] Example 13: 10 layers of P10 degradable anti-inflammatory coating were sprayed on a magnesium alloy substrate, each layer having a thickness of 10 μm.

[0048] Example 14: 10 layers of P7 degradable anti-inflammatory coating were sprayed on a magnesium alloy substrate, each layer having a thickness of 10 μm.

[0049] Example 15: 30 layers of P10 degradable anti-inflammatory coating were sprayed on a magnesium alloy substrate, each layer having a thickness of 10 μm.

[0050] Example 16: 30 layers of P7 degradable anti-inflammatory coating were sprayed on a magnesium alloy substrate, each layer having a thickness of 10 μm.

[0051] Example 17: 30 layers of P10 and P7 degradable anti-inflammatory coatings are sprayed alternately on a magnesium alloy substrate, that is, 15 layers of P10 and P7 coatings respectively, and the thickness of each layer is 10 μm.

[0052] Each sprayed layer was dried before the next layer was sprayed. Comparative Example 1 was selected as a comparison, i.e., the magnesium alloy substrate without the sprayed degradable anti-inflammatory coating was used as a comparison. 13 samples were made in each group, and the samples were immersed in artificial plasma, which was replaced every 24 hours. The fracture toughness of the samples was tested every 30 days according to JB / T 12616-2016, and the unit was MN·m -3 / 2 When the fracture toughness is lower than 50% of the initial fracture toughness, the sample is considered to have failed, and the remaining samples are no longer tested. The specific test results are shown in Table 2 below.

[0053] Table 2 Fracture toughness test results

[0054]

[0055]

[0056] From the above data, it can be seen that the fracture toughness of the control sample without spraying coating was less than 50% at 3 months, and the sample sprayed with 10 layers of coating began to fail at 6-7 months, but the sample sprayed with 30 layers of P7 composition coating can still maintain a high fracture toughness after 12 months, indicating that the degradable anti-inflammatory coating can better protect the magnesium alloy substrate, and bone plate products with different degradation rates can be obtained by adjusting the combination of the coating, and the anti-inflammatory drugs contained in the coating can be released at the expected rate to meet the usage needs of different patients.

[0057] In addition, the initial fracture toughness of all coated magnesium alloy substrates is higher than that of the control samples, indicating that the polylactic acid anti-inflammatory coating has a certain effect on improving the fracture toughness of the magnesium alloy substrate.

[0058] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A degradable anti-inflammatory bone plate, characterized in that: The invention comprises a magnesium alloy substrate and a polylactic acid anti-inflammatory coating coated on the surface of the magnesium alloy substrate.

2. The degradable anti-inflammatory bone plate according to claim 1, characterized in that: The polylactic acid anti-inflammatory coating has 1 to 30 layers.

3. The degradable anti-inflammatory bone plate according to claim 1, characterized in that: The thickness of the polylactic acid anti-inflammatory coating is 5-300 μm.

4. The degradable anti-inflammatory bone plate according to claim 1, characterized in that: The polylactic acid anti-inflammatory coating is a blend of polylactic acid and anti-inflammatory drugs, wherein the weight average molecular weight of the polylactic acid is 50,000-300,000, the molecular weight distribution index is 1.5-5.0, the polymer tailing index in the molecular weight distribution width is greater than 2.5, and the molecular weight and molecular weight distribution width of the polylactic acid used in each layer of the coating are different.

5. The degradable anti-inflammatory bone plate according to claim 4, characterized in that: The degradation time of each polylactic acid anti-inflammatory coating is different.

6. The degradable anti-inflammatory bone plate according to claim 4, characterized in that: The anti-inflammatory drug is one or more combinations of aspirin, naproxen, indomethacin, meloxicam, celecoxib, diclofenac sodium, nimesulide and etoricoxib.

7. The degradable anti-inflammatory bone plate according to claim 1, characterized in that: The magnesium alloy matrix has a zinc content of no more than 0.20wt%, a lithium content of no more than 0.20wt%, a manganese content of no more than 0.15wt%, a copper content of no more than 0.03wt%, an iron content of no more than 0.01wt%, a silicon content of no more than 0.01wt%, and a nickel content of no more than 0.005wt%.

8. The method for preparing a degradable anti-inflammatory bone plate according to claim 1, characterized in that: The steps include: S1: Dehydrating the lactic acid raw material at 110-140° C. for 5-8 hours to obtain lactic acid oligomers, adding a catalyst to the lactic acid oligomers at 100-120° C. under inert atmosphere and stirring for 2 hours, and then heating to 160-200° C. and polycondensing under vacuum for 10-20 hours to obtain polylactic acid, wherein the catalyst is any one of tin chloride, stannous chloride, and stannous lactate; S2: by adjusting the reaction temperature and time during polycondensation, polylactic acid with different molecular weights and molecular weight distribution widths is obtained, and polylactic acid with a weight average molecular weight of 50,000-300,000, a molecular weight distribution index of 1.5-5.0, and a high molecular weight tailing index in the molecular weight distribution width greater than 2.5 is screened; S3: blending the polylactic acid screened in S2 with an anti-inflammatory drug, and spraying the blend onto the surface of the magnesium alloy substrate by ultrasonic spraying, with a spraying thickness of 5-10 μm; S4: placing the magnesium alloy substrate sprayed with the degradable anti-inflammatory coating in a simulated human body environment, testing the degradation time of each composition, and numbering the polylactic acid and anti-inflammatory drug blends as P1, P2, ... P10 according to the degradation time from short to long, and finally screening 10 groups of mixtures; S5: Take the prepared magnesium alloy substrate, and according to specific usage requirements, use ultrasonic spraying to spray 1-30 layers of the composition of polylactic acid and anti-inflammatory drugs on the magnesium alloy substrate. According to specific usage requirements, select a suitable combination from P1, P2...P10 and spray them in order to obtain a degradable anti-inflammatory bone plate.

Citation Information

Patent Citations

  • Preparation method of controlled degradable magnesium alloy fixing screw in vivo

    CN108714252A

  • Degradable bone fracture plate system and preparation method and control method thereof

    CN117770928A